Administration of the Islamic Judicial System: An Overview - Jasri Jamal (Fakultas Hukum Universitas Gadjah Mada, 2010)
Justice in Islam is all-embracing, free from restriction, and universal. Islam governs private and public life, denies deviation from justice, non-discriminative, and holds that all humans are equal before the law and are accountable for their deeds. It is universal because it is applicable to all who accepts its authority. Islam memandang keadilan sebagai sistem yang utuh, bebas dari pembatasan, dan universal. Islam mengatur kehidupan pribadi dan umum, mengajarkan untuk tidak menyimpang dari keadilan, tidak diskriminatif, dan memandang manusia sama di hadapan hukum serta bertanggungjawab atas perbuatannya. Keadilan dalam Islam universal karena berlaku bagi semua manusia yang menundukkan diri padanya.